EFFECT OF ACETAMIPRID RESIDUES IN TOMATO FRUITS ON SOME BLOOD PROFILE PARAMETERS OF MALE MICE - &et al., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Acetamiprid is one of the most wide used insecticides over the entire world. Three acetamiprid concentrations, the dependence one (200 ppm) and two other high concentrations (300 and 400 ppm) were used to treated tomato fruits at the final stage of ripening. A daily samples up to 15 days, were examined for their acetamiprid residues. The maximum migration of acetamiprid (systemic) into tomato fruit was observed after three days (1.7, 1.89 and 2.27ppm) of spraying by 200, 300, and 400 ppm. After 7 days of application, the acetamiprid residues are more than five-fold of the Maximum Residue Limit (acetamiprid MRL=0.2 mg/kg). Four groups of male mice (each of 10, control and three treatments) were used to study the effects of acetamiprid on some blood profile parameters. Three selected concentrations of acetamiprid 32, 64 and 128 ppm were used to orally administrate the male mice (0.0064, 0.0128 and 0.0256 mg/mouse daily respectively) under controlled conditions for 28 days. It was found that there was a direct relationship between acetamiprid concentrations and triglycerides, total cholesterol, LDL, VLDL, catalase, malondialdehyde, urea, creatinine, AST, ALT and superoxide dismutase level. While, reverse relationships were observed with HDL, LH, FSH, testosterone and acetyl cholinesterase